Dream life matchmaker - Subramaniam Chetty, Nithya Dewi; Aman, Hannani; Mohd Yunus, Mohd Amin; Mustapha, Aida (Penerbit UTHM, 2017)
Marriages are arranged by will of the Almighty and by His decisions in the heaven, but the result can only be fruitful if couple were able to meet real- life partner and establish a permanent relationship between them. Matchmaker system is the medium to help join two people through which both people will spend their life till their last breath. Matchmaker system is proposed to help individual search for their life partner by specifying a number of personality question so the system able to make recommendation of potential bride/groom. This project contains the detailed information of the person and his/her family and their expectations. This project can help number of people in finding their partners across the country.